Utilising Bacchi's what's the problem represented to be? (WPR) approach to analyse national school exclusion policy in England and Scotland: a worked example - Tawell, A; McCluskey, G (Taylor and Francis, 2021)
This paper examines and compares national policies on school exclusion, using a specific framework for public policy analysis developed by Carol Bacchi [(2009). Analysing policy: What’s the problem represented to be? Frenchs Forest: Pearson]. This framework is known as ‘What’s the problem represented to be?’ or ‘WPR’. Bacchi’s framework has been applied to areas of policy as diverse as health care, labour markets, immigration and higher education, but its use in school-based education has been much more limited to date. Noting too, that the WPR framework itself is rarely interrogated or critiqued in the literature, our small-scale study therefore addresses two main objectives: (a) to offer an illustration, a worked example, of WPR in education as a contribution to methodological debate, and (b) to critically appraise the WPR approach, and its potential to acknowledge, challenge and disrupt normalising discourses within one key area of school-based policy – school exclusion.